Baltic shells: on the mechanics of trade-based money-laundering in the former Soviet space. Issue 1 (5th January 2015) - Stack, Graham
Abstract : Purpose: – The purpose of this paper is to describe a platform of interconnected international shell companies operated through Baltic banks, used for trade-based money laundering (TBML) across Russia, Ukraine and other post-Soviet states. Design/methodology/approach: – This is a case study that draws extensively on the results of journalist investigations and court cases to describe one example of a money-laundering platform. Findings: – Platforms of international shell companies operated through Baltic banks play a key role in TBML for the post-Soviet countries. They are created for systematic laundering of revenues from tax evasion, tax fraud, corruption and criminality across the post-Soviet space, and also globally. Research limitations/implications: – This study implies that TBML for the post-Soviet space is a specialized industry, hosted by collaborating banks centered in the Baltic states, in conjunction with mass use of international shell companies. Practical implications: – This study implies that analysis of suspicious transactions cannot remain on the level of single companies but has to take into account the interconnected payment patterns produced by such a platform. Originality/value: – Provides the first study of a trade-based money-laundering platform operating in the post-Soviet space.